The Benefits and Limitations of a Behavioral Intervention for Caregivers of Dementia Patients: A Qualitative Study. Issue 3 (August 2019) - Nehrig, Nicole; Shifrin, Maria; Abraham, Karen; Chen, Cory K.
Abstract: This study used qualitative methods to understand dementia caregivers' experience of personal and therapeutic factors contributing to outcome following REACH VA, a behavioral intervention designed to alleviate caregiver burden and depressive symptoms. Caregivers and their interventionists were queried about their experiences of the treatment in semistructured interviews. Interviews were transcribed and analyzed using thematic analysis. The following themes emerged reflecting aspects of the intervention caregivers and interventionists found helpful: self-care, shared goals, psychoeducation, and stress-management skills. Some caregivers and interventionists found the provision of problem-solving skills to be helpful and others did not. Finally, some caregivers and interventionists reported that interpersonal support/bearing witness, insight, emotional transformation, and the discussion of interpersonal process were useful when part of the intervention or, when not included, would have been helpful. While behavioral interventions tend to be highly structured, interventionists' ability to work flexibly within the protocol and tailor it to the caregiver's needs was related to positive treatment response. The beneficial aspects of this treatment represent multiple theoretical orientations highlighting the importance of transtheoretical models of therapeutic action. Highlights: Caregivers valued discussing their difficulties and many wished for more support. Responders appeared more solution-focused and motivated to implement new skills. Nonresponders often wanted more emotional support than the intervention offered. A flexible approach to structured interventions for caregivers is indicated.